2022
DOI: 10.1002/hed.27007
|View full text |Cite
|
Sign up to set email alerts
|

Tumor molecular differences associated with outcome disparities of Black patients with head and neck cancer

Abstract: Background Numerous studies of head and neck squamous cell carcinoma (HNSCC) have demonstrated disparate outcomes by race and ethnicity. Beyond known associations with socioeconomic variables, whether these are also associated with differences in tumor molecular composition has thus far been poorly explored. Methods We downloaded clinical and multiplatform molecular data from The Cancer Genome Atlas and other published studies. These were compared between non‐Hispanic Black (n = 43) and White (n = 354) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…We selected covariates that were identical to those use in our previous peer reviewed analyses. This allows us to directly compare the model estimates with our prior work 18–21 . As a final note, our findings of molecular and survival differences are associative, and in some cases the significance is unclear.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We selected covariates that were identical to those use in our previous peer reviewed analyses. This allows us to directly compare the model estimates with our prior work 18–21 . As a final note, our findings of molecular and survival differences are associative, and in some cases the significance is unclear.…”
Section: Discussionmentioning
confidence: 87%
“…The mRNA abundance profiles of tumors positive and negative for each pathological feature were modeled as negative binomial generalized linear distributions and compared using a Wald test with shrinking of log 2 fold‐change values within the DESeq2 program. FDR adjustment was done as previously described 16–21 . Genes with significantly different mRNA expression were analyzed for pathway over‐representation using Reactome Pathway Analysis 30 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaudhary and colleagues used the cancer genome atlas and cancer digital archive of HNSCC patient and showed that Black patients had a higher frequency of mutations in several genes such as P53 and FATI, and showed less intra-tumoral infiltration of the effector immune cells [ 31 ]. Another study comparing mutational differences between Black and White HNSCC patients showed a greater number of copy aberrations and increased miRNA-mediated PRG4 silencing [ 32 ]. Future studies should continue to investigate the biological markers and drivers of disease in R/E minorities, which may elucidate opportunities for personalized medicine in these specific populations.…”
Section: Discussionmentioning
confidence: 99%